Al-‘Urf and Al-‘Adah al-Muḥakkamah as The Methodology of Istinbāṭ of Islamic Law: A Thematic Analysis from The Perspective of Sharia Economic Law - Mualim; Chaerul Shaleh; Aden Rosadi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Purpose – This research aims to analyze the position and function of al-‘urf and al-‘ādah al-muḥakkamah as a methodology for Islamic legal istinbāṭ, particularly in the context of the development of Sharia Economic Law that is responsive to contemporary social dynamics and economic practices. This research begins with the epistemological question of the extent to which social customs can obtain sharia legitimacy in establishing modern muamalah law. Method – The method used is qualitative research through library research with normative-juridical, philosophical, and comparative approaches to Islamic schools. Data are analyzed thematically against classical and contemporary sources of ushul fiqh, as well as Sharia economic law literature, to map the position of al-‘urf within the framework of the ijtihad methodology. Result – The results show that authentic al-‘urf has legal legitimacy if it meets the criteria of conformity with the maqāṣid al-syarīah, does not conflict with the qath’i texts, and is generally applicable and consistent in muamalah practices. A comparative study of Islamic schools of thought reveals that despite differences in the intensity of its acceptance, all Islamic schools of thought recognize al-‘urf as a valid instrument of ijtihad. In the realm of Islamic Economic Law, al-‘urf and al-‘ādah al-muḥakkamah have proven to play a strategic role in responding to contract practices, market customs, and modern transaction innovations. Implication – The implications of this research emphasize the importance of strengthening al-‘urf as a methodology for legal istinbāṭ, not merely as a supplementary argument, to ensure that Islamic economic law remains adaptive, contextual, and oriented toward the welfare of the people.